Evaluation of good review practices in member authorities of the East African Medicines Regulatory Harmonisation initiative: strategies for alignment with African medicines agency - Ngum, Nancy; Ndomondo-Sigonda, Margareth; Habonimana, Rémy; Siyoi, Fred; Irasabwa, Clarisse; Ojukwu, Julia; Apolinary, Felchism; Okello, Andrew; Ahmada, Sabrina; Walker, Stuart; Salek, Sam (Frontiers in Medicine, 2024)
The East African Community Medicines Regulatory Harmonization (EAC-MRH) programme was established to address challenges faced by national regulatory authorities (NRAs) of the region. Work sharing through joint assessments and inspections was adopted to manage limited resources and capacity; however, NRA good review practices (GrevP) are also a key determinant to success. This study evaluated GReVP among the EAC-MRH NRAs and mapped required strategies for countries to align themselves with the African Medicines Agency (AMA).A validated questionnaire (Optimising Efficiency in Regulatory Agency -OpERA) that standardises and captures review processes was completed by 42 heads of the medicines registration division in each NRA. A country report based on the completed questionnaire was developed for each NRA and validated by the heads of the respective authorities.The population and size of the NRAs vary and four of the countries have semi-autonomous authorities and three NRAs are autonomous. The Burundi and South Sudan authorities were fully government funded, Kenya and Uganda entirely from fees, while Rwanda, Tanzania and Zanzibar were partially funded from different sources. All authorities except South Sudan, which does not receive or review applications had backlogs. Authority fees varied based on the different application categories. Key milestones for standardised regulatory processes are implemented in all authorities. Queue times range from a few weeks to about one year. Three NRAs use internal technical agency staff for scientific assessments and three use both internal and external experts. Clock stop time varies and target timelines for review committee range from one day to three months. All the NRAs implement some best practices on quality measures, transparency and communication. Some have activities for transparency improvement but with minimal attention to training and education. Most employ some quality decision-making practices.GrevP in EAC-MRH NRAs still needs to be improved and it is imperative that these authorities streamline and harmonise their practices. Increasing human resources and an investment in training and education of staff will enable the implementation of all measures for GRevP. This is vital, as the effectiveness and efficiency of the AMA will depend on the strength of these NRAs.